AVALIAÇÃO COMO INSTRUMENTO DE APRENDIZAGEM: O 1º ano do 1º ciclo do ensino fundamental em foco - SOUTO, Maria Raimunda Ferreira (2024)
The general purpose of this research was to analyze the practice of teachers as evaluators in the process of teaching and learning of students in the first year of elementary school Lindalva Pinho. We take as focus of analysis the teachers and the evaluation methods instituted in pedagogical practice. We ask how teachers evaluate the teaching and learning process of students in the first year of elementary school Lindalva Pinho? The theoretical reference anchored in Luckesi (2006, 2000), Hoffmann (2002, 2005, 1995), among others that approach the evaluation of learning. Data collection was performed through the questionnaire. We conclude that reflexive analyzes of teachers are carried out spontaneously through observations and the accomplishment of diagnoses about students 'previous knowledge, the evaluation is conceived as a continuous process and aims at students' learning.